PARENTING AND LABOR ACTIVITY - Mariа RADEVA (Challenges of the Knowledge Society)
In recent years there has been a public debate in Bulgaria about the reconciliation of childcare and the preservation of labor activity. The government policy regarding maternity support is broadly discussed - length of absence, job retention, salary level, career opportunities, etc. The state has proposed measures to ensure that parents return to the labor market. One option is to return to work before the end of maternity leave. The resources for implementing this policy are provided to the social security system. The Employment Agency is carrying out a project aimed at ensuring a better reconciliation of the professional and private life of parents with children from 0 to 12 years of age. The desired result is to have a positive effect by preserving the quality of workforce and labor productivity of parents by enabling them to start or continue their careers. The project is implemented with funds from the European Social Fund and national co-financing.